Effectiveness of low‑temperature storage on lipid nutritional quality of fish: A meta‑analysis - Tan, Karsoon; Huang, Leiheng; Choong, Luo Khai Hang; Leong, Seng Lim; Peng, Xu; Kit, Leong Cheong (Springer Nature, 2025)
Fish are rich in n-3 long-chain polyunsaturated fatty acids, which provide numerous health benefits. Proper food storage methods, especially low-temperature storage, are crucial for maintaining the lipid nutritional quality of seafood. While numerous studies have examined the effects of low-temperature storage on fish lipids, the information remain poorly organized, and many important detail (such as various lipid nutritional quality indices) have not been systematically analyzed in most studies. To address this gap, this study conducted a meta-analysis to evaluate the effects of short-term and long-term low-temperature storage on the lipid nutritional quality of fish. The results of this study are particularly valuable as they provide practical guidance to consumers for selecting optimal low-temperature storage methods to better preserve the quality of fish lipids.